PENGARUH AGENCY COST TERHADAP KINERJA KEUANGAN PERUSAHAAN KELUARGA MENGGUNAKAN TOBIN’S Q & ALTMAN Z-SCORE - Manalu, Sahala; Natalia, Sheren (Jurnal Ekonomi Modernisasi, 2015)
this research aims to test the effect of agency cost toward financial performance in family business measured by Tobin’s Q and Altman Z-Score with proxied by insider ownership, dispersion ownership, institutional ownership. This research was conducted at family business firms listed in Indonesian Stock Exchange from 2010-2014. In this research, multiple linear regression analysis were used. The result show the agency cost (insider ownership, dispersion ownership, institutional ownership) simultaneously have a significant effect toward Tobin’s Q, insider ownership and institutional ownership are not significant toward Tobin’s Q, dispersion ownership has a significant effect toward Tobin’s Q, agency cost (insider ownership, dispersion ownership, institutional ownership) simultaneously and partial are not significant toward Altman Z-Score.